ANALISIS NILAI BUDAYA SIRIK NA PACCE DALAM FILM ANAK KARAENG KARYA YUS AMIN DB - Novidayanti; Daeng, Kembong; Yunus, Andi Fatimah (Journal Studies in Indonesian Language and Literature, 2024)
The purpose of this study is to describe the cultural value of sirik na pacce in the movie Anak Karaeng by Yus Amin Db using the theory according to Abu Hamid in this study using observation techniques and document studies. The results of this study indicate that (1) the form of sirik in the movie Anak Karaeng by Yus Amin Db there are three categories of sirik, namely, first sirik pakasirik is sirik related to personal self-esteem, as well as self-esteem or family dignity. The second sirik mappakasirik sirik is a type of sirik related to work ethic. The third sirik tappela' sirik is a person's sense of shame that is lost